Brand Cultures: Between Identity and Image - Barbu, Oana (Mediterranean Journal of Social Sciences, 2012)
This paper will try to analyze the role played by branding communication in the â€œeducationâ€ of the masses, on socialresponsibility and at a level of micro cultural trends. The main purpose of this paper is to analyze the formation of symbolic meaning inbrand to consumer communication starting from the concepts of brand identity and brand image. We advance the hypothesis that themeaning of brand communication depends to a large extent on the â€œcultureâ€ developed by a markâ€™s symbolic functions.